2019
DOI: 10.1136/bmjqs-2019-009537
|View full text |Cite
|
Sign up to set email alerts
|

Hospital-level evaluation of the effect of a national quality improvement programme: time-series analysis of registry data

Abstract: Background and objectivesA clinical trial in 93 NHS hospitals evaluated a quality improvement programme for emergency abdominal surgery, designed to improve mortality by improving the patient care pathway. Large variation was observed in implementation approaches and the main trial result showed no mortality reduction. Our objective therefore was to evaluate whether trial participation led to care-pathway implementation and to study the relationship between care-pathway implementation and use of six recommende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 35 publications
0
20
0
Order By: Relevance
“…The QI programme in the EPOCH trial required an extensive care pathway with 37 components to be implemented (9) and there were wide variations in these elements at individual hospitals and thus local adaptations in each hospital were needed. According to the ethnographic evaluation of this QI programme (32), hospital staff often had little or no additional time to improve patient care and consequently, the objective of the EPOCH QI programme was not readily achieved because the care pathway was not implemented as fully as intended (33). As such the lack of cost-effectiveness identified here may be due, to a large extent, on implementation failure resulting in a loss of intervention effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…The QI programme in the EPOCH trial required an extensive care pathway with 37 components to be implemented (9) and there were wide variations in these elements at individual hospitals and thus local adaptations in each hospital were needed. According to the ethnographic evaluation of this QI programme (32), hospital staff often had little or no additional time to improve patient care and consequently, the objective of the EPOCH QI programme was not readily achieved because the care pathway was not implemented as fully as intended (33). As such the lack of cost-effectiveness identified here may be due, to a large extent, on implementation failure resulting in a loss of intervention effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the study designs described by Foy et al, an understanding of relevant contextual factors using qualitative methods can help explain how national audits are perceived locally and used for improvement (or not). Recent evaluations of a quality improvement intervention in the UK using data from the National Emergency Laparotomy Audit, for example, showed the importance of social barriers to change 234…”
mentioning
confidence: 99%
“…In this issue of BMJ Quality and Safety, Stephens and colleagues provide insight into the first problem of ineffective implementation. 4 The authors used a hospitallevel time-series analysis and run charts to determine whether or not participation in the EPOCH trial led to actual changes in the 10 processes of care targeted by trial. 4 They also characterised the relationship between care-pathway implementation and the use of six suggested implementation strategies.…”
mentioning
confidence: 99%
“…4 The authors used a hospitallevel time-series analysis and run charts to determine whether or not participation in the EPOCH trial led to actual changes in the 10 processes of care targeted by trial. 4 They also characterised the relationship between care-pathway implementation and the use of six suggested implementation strategies. Ultimately, they found that only a small number of hospitals improved even half of the 10 targeted processes, but the greatest number of process improvements occurred at the hospitals that used five or more of the suggested implementation strategies.…”
mentioning
confidence: 99%
See 1 more Smart Citation